E3RC: A step-by-step computational protocol for exploring enhancer RNA expression and regulation using conventional RNA-seq data - Hua Yu; Yunjie Liu; Zhouming Zhang; Guanglei Xie; Jingyu Liu; Yijia Liu; Siyue He; Zhiwei Peng; Lu Lu; Fei Li; Xi Wang (STAR Protocols, 2025)
Summary: Here, we present a computational framework, E3RC, for exploring enhancer RNA (eRNA) expression and regulation using conventional RNA sequencing (RNA-seq) data. Using a public dataset as an example, we describe step-by-step guidelines for identifying eRNAs and characterizing their expressional changes and transcriptional regulation across multiple developmental stages of mouse preimplantation embryos.For complete details on the use and execution of this protocol, please refer to Yu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.